Be more, do more, research more: The importance of developing local science - Lüscher, Thomas F. (2020)
There were times when our ancestors lived in a dangerous environment. Indeed, primates including homo sapiens and its predecessors were neither strong nor particularly fast. They were an easy prey for predators: but they were smart and became eventually the dominant species. Why could this happen? First, they developed the concept of cause and effect, they learned to see events in causal terms, that one event followed another consistently and they used this to shape their environment – this made them the tool makers of the evolution. Then they discovered how to make fire and weapons and suddenly they were no longer a prey, but predators themselves. Finally, they learned to work together, to communicate, to talk to and inform each other about dangers and opportunities and to pursue them together. Working together was a key-success-factor of these social animals who alone would not have survived the struggle for survival. Thus, rational thinking, communicating with each other and working together made us the dominant species. What brought humans forward? The ambition to be more and to do more.